Consumption of fruits and vegetables among Peruvian adults: Analysis of a national health survey 2017-2018. - Wilmer Cristobal Guzman-Vilca; Rodrigo M Carrillo-Larco; Carla Tarazona-Meza (PLOS Global Public Health)
The WHO recommends consuming ≥400 g/day of fruits and vegetables daily as part of a healthy diet to prevent non-communicable diseases (NCDs). Data on fruits and vegetables intake is scarce in several countries, including Peru. However, it remains crucial to monitor policies to reduce the burden of non-communicable diseases. Cross-sectional analysis of a representative at the national level survey of Peruvian adults conducted in 2017-2018. Consumption of fruits and vegetables, stratified by socio-demographic and health-related variables, was estimated from a single 24-hour dietary recall questionnaire. Regression models were conducted to assess the potential association with low consumption of fruits and vegetables. The mean consumption of fruits and vegetables was 153.8 (95% CI: 133.4-174.2) g/day. Only 13.6% of the population consumed ≥400 g/day of fruits and vegetables. People with obesity (120 g/day), unaware diabetes (79.6 g/day) and unaware hypertension (51.1 g/day) had the lowest mean consumption. A consumption of <400 g/day was associated with obesity (OR): 2.56 (95% CI: 1.22-5.37) and having hypertension (OR: 3.32 (95% CI: 1.16-9.5)). Only 14 out of 100 Peruvian adults consume the recommended daily amount of fruits and vegetables and the mean consumption of fruits and vegetables is less than 2 portions a day. There is an urgent need for multi-sectoral health policies focused on increasing the access and consumption of fruits and vegetables as part of a healthy diet to reduce the burden of NCDs.